Exploration of RMP ELM control on ITER-similar shape (ISS) in KSTAR. (29th October 2021) - Hahn, Sang-hee; In, Y.; Eidietis, N.W.; Juhn, J.W.; Kang, J.; Kim, M.; Ko, W.H.; Lee, J.K.; Lee, M.W.; Lee, Y.H.; Shin, G.W.; Barr, J.; et al.
Abstract: Recent control advances at KSTAR enabled us to not only establish but also to sustain the ITER-similar shape (ISS) in a stationary manner, matching the ITER-like dimensionless shape parameters in lower single null configuration with vastly contrasting upper/lower triangularities. The kinetic parameters of the ISS are different from the typical KSTAR configurations seen in ELM-RMP suppression experiments. We experimentally demonstrate the ISS-compatible resonant magnetic perturbation (RMP) control in KSTAR for the first time, using the n = 2, +90 degrees phasing RMP.